BANANA CANDY PRODUCTION IN A SMALL AGROINDUSTRY LOCATED IN GUARAQUEÇABA-PR - MACCARI JÚNIOR, Agenor; SOUZA, Jorge Luiz Moretti de; BITTENCOURT, Jefferson (Scientia Agraria, 2007)
The objective of this work was to analyze the efficiency of the banana (Group: Cavendish, Class: 6 e 9; Subclass: 4 e 5) peeling and cooking operations in the candy production process. The experiment was carry out in a small agroindustry denominated UTPA Batuva, which was build to promote the sustainable development as well as to aggregate commercial value to the banana production from the Batuva’s community, located in the Environmental Protection Area of Guaraqueçaba-PR. Several studies are being carried to optimize the agroindustry structure and to capacitate the farmers to manage it. In this work, 41 different formulations for banana candy production were tested. The banana peeling and cooking operations in the candy production process were evaluates with regression and correlation analyses. The results showed that: (a) The yield relationships followed linear tendencies; (b) In average, 100 kg of banana fresh fruit resulted in 66.7 kg of banana pulp and 19.31 kg of banana candy; (c) The candy production evaluated by the quantity of banana pulp versus cooking time was more efficient when the capacity of the pan worked above the limit projected.